Analisis Pendapatan Usahatani Bunga Anthurium (Anthurium andraeanum sp) Di Kelurahan Kakaskasen Kota Tomohon - Sembiring, Viona Agnes; Baroleh, Jenny; Lolowang, Tommy Ferdy (AGRI-SOSIOEKONOMI, 2024)
This research aims to determine and analyze the income of Anthurium andraeanum flower farming in Kakaskasen Village, North Tomohon District, Tomohon City. The research took place from May to August 2023. The data collected was primary data obtained directly from Anthurium andraeanum flower farmers and secondary data obtained from research results and journals. Sampling used a purposive sampling method, namely farmers who cultivated Anthurium andraeanum ornamental flower plants were selected. In this research, the population of farmers cultivating Anthurium andraeanum flower plants was 2 farmers. The results of the research show that Anthurium andraeanum flower farming in Kakaskasen Village, Tomohon City with an average land area of 450 m2 = 0.045 ha, this farming incurs total costs in one planting season of Rp851,500 with receipts of Rp1,800,000 per 2 weeks (15 days) and get a total income of Rp948,500 per farm for one harvest every 2 weeks. The average R/C ratio is 2.11, which is greater than 1, meaning that flower farming is profitable and worthy of cultivation and development.